Analysis of Zakat Performance of Central Java Province - Isro’iyatul Mubarokah; Irfan Syauqi Beik; Tony Irawan (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
The Indonesian province with the third largest Muslim population is Central Java. This suggests a great potential for zakat collection. However, the amount accumulated is far from significant. This study aims to determine zakat performance in Central Java Province at macro and micro levels. Data collectioninvolved distributing questionnaires during interviews. This study employeda convenience sampling technique. The analytical tool used in this research is National Zakat Index (NZI).National Zakat Index is an indicator that illustrates the extent to which charity has been instrumental to the mustahikwelfare. It also indicatesthe initial stages of zakat development in terms of internally and at a community level, as well as highlight the support provided by the government. Findingsindicate that zakat performance of Central Java Province from a macro dimension is poor, while from a micro prospective it is decent. Keywords: macro dimension, micro dimension, National Zakat Index (NZI), zakat performance